ANALISIS WEBSITE SEKOLAH MENENGAH KEJURUAN (SMK) DI JAWA BARAT - Subagja, Handa (2017)
Statistik mengenai kondisi website sekolah masih sulit didapatkan. Penelitian ini bertujuan untuk mengetahui kualitas website yang ditinjau dari kelengkapan kriteria isi pada website Sekolah Menegah Kejuruan (SMK) di Jawa Barat. Metode penelitian yang digunakan adalah analisis isi dan survei. Hasil penelitian ini menunjukkan rata-rata kualitas website SMKN di Jawa Barat masih rendah. Rekomendasinya adalah dibutuhkan peningkatan kualitas website sekolah. Kata kunci: kualitas website, kriteria website sekolah, SMK Statistics about the condition of the school's website is still difficult to obtain. This study aims to determine website quality in terms of completeness of content's criteria of Vocational High School (SMK) in West Java. The method used is the content analysis and survey. The results of this study showed the average quality of the website SMKN in West Java is still low. The recommendations are needed to improve the quality of the school website. Keywords: quality of website, criteria of school website, vocational high school